Latar Sosial dalam Novel Rentang Kisah Karya Gita Savitri Devi - Putri Takbirotul Dewi Ariswati; Ida Bagus Jelantik (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The social setting in the novel Rentang Kisah by Gita Savitri Devi tells the story of Gita's life living the lecture period abroad alone, behind it is also told about the spiritual journey of the main character in rediscovering Islam. the novel Rentang Kisah was chosen as the object of research because this novel contains a lot of learning and motivation about the world of lectures and religion, especially Islam. this study aims to analyze: (1) the structure of the novel based on plot, character, and setting. (2) describe in detail about the social setting. The theories used in this research are (1) Teeuw's structural theory, and (2) Nurgiyantoro's social setting. the methods used for data collection are reading, and note-taking techniques. then the results are analyzed using descriptive qualitative. The results of this study consist of two parts, namely structural studies and social settings. First, the structural study of the novel Rentang Kisah has three stages of the plot in the story by using a mixed plot (forward-backward), including the initial stage, middle stage, and final stage. The social setting in the novel Rentang Kisah by Gita Savitri Devi includes Gita's life from looking for dreams and passions that match the college she will choose. In the end, Gita decided to study in Berlin, Germany. The social environment in the novel is the city of Berlin, Germany.The author tells the story of Jakarta, which has undergone some changes after two years of Gita's absence.